Cardiac venous arterialization in acute myocardial infarction: how great is the benefit? - Maria Rodrigues Munz (2013)
Cardiac venous arterialization has been proposed as an alternative approach for myocardial revascularization in ischaemic heart disease. It is based on using the cardiac venous system to transport arterial blood from a systemic artery to infarcted myocardial areas. Our goal was to evaluate its benefit in reducing acute myocardial infarct size and its effects on cardiac performance. In a group of pigs, the left internal mammary artery was anastomosed to the left anterior descending vein; this vein was ligated proximally. The left anterior descending coronary artery was also occluded. Over 5 days, several diagnostic procedures were used to characterize and measure the extent of myocardial infarct, namely ECG, echocardiography, cardiac biomarkers and histopathology. Data were compared with those from a control group of pigs, which were submitted to ligation of only the left anterior descending coronary artery. In the experimental group, echocardiography revealed that the ejection fraction and thickness of the ventricular walls remained unchanged 4 days after surgery, in contrast to the major alterations in the control group. In fact, the ejection fraction in the control group decreased by 21% (P < 0.001), with a reduction of 31% (P < 0.004) in the thickness of the interventricular septum at end systole and enlargement of the left ventricular lumen by 28% (P < 0.001). In the experimental group, the sum for ST segment shift was 50% lower (P = 0.038) and the total ventricular histological lesion size was 50% smaller (P < 0.001). Within this lesion, the area of necrotic tissue was 70% smaller (P < 0.001). Cardiac biomarkers were not different between the two groups (P > 0.2). This study reveals that selective cardiac venous arterialization can nourish the myocardium and is able to reduce infarct size by more than 50%, while protecting cardiac performance. We believe, therefore, that further investigation should be carried out into this technique in order for it to be considered as an option in coronary surgery.